Laparoscopic Management of Ectopic Pregnancies - Duggal, BS (Med J Armed Forces India, 2004)
To compare the laparoscopic approach with laparotomy in the treatment of ectopic pregnancy, a retrospective analysis involving 52 patients with ectopic pregnancies was done. The aim of this study was to evaluate the safety and efficacy of laparoscopic surgery for ectopic pregnancies. 30 patients underwent laparoscopic management while 22 patients were managed by conventional laparotomy. In the laparoscopic group, the postoperative morbidity and post-hospital stay were significantly less. Although laparoscopic surgery for ectopic pregnancies is a new approach and it is not widely practised in service hospitals, it has more advantages than open surgery and it has been well accepted by the surgeons and patients. It is a safe and feasible approach.